Multiple deprotonation of primary aromatic diamines by LiAlH41. Issue 9 (7th March 2015) - Less, Robert J.; Allen, Lucy K.; Steiner, Alexander; Wright, Dominic S.
<x xml:space="preserve">Abstract</x> Reaction of LiAlH4 with 1, 2-phenylenediamine (1H4) in THF gives [{Al(1H2)}2{Al(1H)2}2][Li(THF)2]4, containing the largest aluminate of its type so far reported.